Designing Donation Incentive Contracts for Online Gig Workers - Tommaso Reggiani; Rainer Michael Rilke (Journal of Business Ethics, 2023)
This study examines the effects of donation incentives on labor supply in an online labor market through a field experiment ( n 0.167em=0.167em944). We manipulate the donation purpose of the incentive to be either unifying or polarizing and the size of the donation relative to the workers' wage. Our experimental design allows us to observe the decision to accept a job (extensive margin) and different dimensions of productivity (intensive margin). We predict and show that a unifying donation purpose attracts more gig workers and improves their productivity compared to a polarizing donation purpose. We discuss the implications of these results in order to understand the role of donation incentives and labor supply in online labor markets.
Keywords: C93; D23; M52; 300; Social incentives; Labor supply; Online gig working; Experiment